Rationale and feasibility of a rapid integral biomarker program that informs immune-oncology clinical trials: the ADVISE trial - Akshita Gupta; Riyue Bao; F Stephen Hodi; Jaclyn Neely; Jason J Luke; Ashish Massey; Santanu Dutta; Janis Taube; George Lee; Katherine Bever; Peter Szabo; David Yao; et al. (Journal for ImmunoTherapy of Cancer)
Background ADVISE (ADaptiVe biomarker trial that InformS Evolution of therapy) (NCT03335540) was a biomarker-adapted feasibility clinical trial of immunohistochemistry (IHC) to inform combination immuno-oncology (I-O) treatment.Methods To inform I-O combination selection, messenger RNA expression analyses from The Cancer Genome Atlas evaluated associations between programmed death 1/programmed death ligand 1 (PD-1/PD-L1) and other I-O-associated genes. Tumor tissue blocks of melanoma, non-small cell lung cancer, renal cell carcinoma, urothelial carcinoma, squamous cell carcinoma of the head and neck, and gastroesophageal junction/gastric cancer were stained by IHC to assess expression of CD8, colony-stimulating factor 1 receptor, glucocorticoid-induced tumor necrosis factor receptor (GITR), indoleamine 2,3-dioxygenase 1, lymphocyte-activation gene 3, NKp46, forkhead box P3, and PD-L1. These results facilitated an I-O treatment selection algorithm where patient biopsy results dictated allocation into combinations of nivolumab with cabiralizumab, urelumab, linrodostat mesylate, relatlimab, BMS-986156 (anti-GITR), lirilumab, ipilimumab, or irradiation. The primary endpoint was the proportion of patients with qualified baseline tumor biopsy specimens where decision-enabling biomarker analysis was completed within 12 business days to select an I-O combination therapy.Results Correlation of PD-1/L1 and I-O-associated genes varied across the spectrum of T-cell-inflamed versus non-inflamed tumors; however, tumors with low/intermediate PD-L1 expression demonstrated distinct upregulation of immune markers grouped by cell type (T cell, macrophage, etc). IHC analyses of I-O naïve tumors corroborated these findings with distinct immune target upregulation in low-to-intermediate inflamed tumors and significant associations between IHC-detected markers and T-cell inflammation score across most markers. In the clinical trial, 20/23 (87%) of eligible patients were successfully allocated and started on treatment within the 12-day window, meeting the primary endpoint. The safety profile appeared to generally align with those reported for the individual combinations from other trials. No treatment responses occurred. Most patients were allocated to the cabiralizumab treatment arm.Conclusions Actualization of a patient-specific I-O combination treatment selection strategy is feasible, however, determination of de novo integral biomarker thresholds of novel I-O targets to facilitate effective treatment of PD-1-refractory cancer remains fraught. These data emphasize the difficulty of integral biomarker development for I-O in translating from immunotherapy treatment-naïve biospecimens to the selection of patients in the PD-1-refractory state.Trial registration number NCT03335540.